Short communication: Opportunities and challenges for Peruvian fine flavored cocoa - Cabrera-de-la-Cruz, Lady (2024)
The notable increase in the price of cocoa globally has generated interest both in the scientific community and in the many actors involved in the production chain. The objective of this communication was to collect some opinions on the opportunities and challenges that must be addressed from the perspective of small producers, academia and government. The need to improve native varieties of fine-flavor cocoa to be highly productive and resilient to climate change is discussed, as well as the urgency of effective knowledge transfer from academia in optimizing the conditions of fermentation, drying, and roasting processes, according to cocoa variety and considering producers' conditions. Actions to promote cocoa consumption, such as its inclusion in gastronomy, promotion of its nutraceutical properties, redefinition of fair objectives, and formation of specialized taster schools, are also suggested. Finally, it is noted that it is necessary to clarify state interventions to avoid redundant efforts, as well as to allocate a budget to fulfil the "National Plan for the Development of the Cocoa and Chocolate Production Chain by 2030".